Avatar-User Bond as Meta-Cognitive Experience: Explicating Identification and Embodiment as Cognitive Fluency - Sah, Young June; Rheu, Minjin; Ratan, Rabindra (Frontiers in Psychology, 2021)
Scholars have not reached an agreement on a theoretical foundation on the psychological effect of avatar use. A group of scholars focuses on the perceptual nature of avatar use, proposing that perceiving the self being represented by a visual representation leads to the effects (i.e., Proteus Effect). Another group suggests that social traits in avatars prime users, causing them to behave consistently with the traits (i.e., priming effect). We combine those two theoretical lines and present an alternative approach, hinging on a concept of meta-cognitive experience. The psychological mechanism of the avatar-user bond is explicated as cognitive fluency, a type of meta-cognitive experience pertaining to one's awareness of how readily or easily information is processed. Under this explication, two concepts related to avatar-user bond, identification and embodiment, are understood as the cognitive experience of fluency at the identity and body level, respectively. Existing empirical evidence on the avatar effects is revisited and discussed how this new theoretical framework can be applied.